(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The last decade has seen the Internet of Things (IoT) taking the world by storm. IoT has the ability to provide a wide range of services in real-time without any form of human intervention. Its most recent application is in the field of agriculture and food supply chain management. The use of IoT in agriculture and food supply chain management is expected to boost agriculture production as well as improve the quality of food products supplied to customers among other things. The use of IoT in agriculture and food supply chain management has however, raises several issues and concerns including those relating to privacy.